Exploring the Ecological Distribution and Antibiotic Resistance Profiles of Klebsiella Species in Diverse Environmental Niches - Dunya Talib Mahdi (Journal of Medical Genetics and Clinical Biology, 2024)
Antimicrobial resistance is a growing problem in bacterial pathogens, particularly in hospital-acquired nosocomial infections. Klebsiella is an important pathogen that causes various infections in hospitalized immunocompromised patients. Therefore, this study aims to fill this knowledge gap and provide insights into the correct detection and antibiotic resistance pattern of these organisms. we will investigate the spread of pneumonia bacteria, Klebsiella, isolate and identify it from different environmental sites, including human, soil, and water, also study the characteristics of antibiotic resistance and find similarities and differences between bacterial isolates. Finally, we detect the associated antibiotics resistance gene (CTX-M), using the genetic RT-PCR method. The study provides valuable information on the prevalence of antibiotic resistant Klebsiella spp. in different clinical and environmental sites, which can help in the development of effective strategies to control the spread of these bacteria. The study found that among all 86 isolated strains of Klebsiella spp. it was found that K. pneumoniae represents the major abundant strain in both clinical and environmental samples by percentages 41.5% and 51.5% respectively. It concerns also the highest ESBL production 71.7%, along with 58% CTX-M gene expression